Testosterone profile in older men with Alzheimer's disease - Cristiana Roscito Arenella Dusi; Lílian Schafirovits Morillo; Regina Miksian Magaldi; Adriana Nunes Machado; Sami Liberman; Wilson Jacob Filho (Dementia & Neuropsychologia)
Abstract Evidence suggests low testosterone levels in Alzheimer's disease. Objectives: To compare testosterone levels between older men with and without Alzheimer's disease. Methods: Fourteen men with Alzheimer's disease were compared with twenty eight men without dementia. Demographic variables and clinical profiles were analyzed. Within fifteen days before or after the described evaluation, measures of total testosterone and Sex Hormone Binding Globulin (SHBG) were performed. Free testosterone level was calculated based on total testosterone and SHBG. Quantitative variables were analyzed using Student's t test or Kruskal-Wallis test, while qualitative variables were analyzed using chi-square or Fisher test. Results: Mean age in the Control and Alzheimer's disease groups were 72.0 (SD±4.8) years and 79.3(SD±5.9) years, respectively (p=0.001). Mean schooling between these two groups were 8.78 and (±5.86) years, respectively (p=0.022). There were no statistically significant differences between the two groups for testosterone levels, although a trend was observed for the Alzheimer's disease group to present lower levels than the control group (p=0.066). There was no direct correlation between free testosterone and age, although a trend was evident (p=0.068). Conclusions: There was no significant difference in testosterone between men with AD and those without dementia.